EVALUASI ALAT PENGADUK DODOL NANGKA SKALA RUMAH TANGGA BERDASARKAN PRINSIP ERGO-EKONOMI : EVALUATION OF HOUSEHOLD SCALE JACKFRUIT DODOL MIXER TOOL BASED ON ERGO-ECONOMIC PRINCIPLES - Bawa Susana, I Gede; Alit, Ida Bagus (Energy, Materials and Product Design, 2024)
The use of manual tools in the process of stirring jackfruit dodol tends to have an impact on high workload, fatigue, and complaints from workers. The stirring process requires a lot of energy to get perfectly cooked dodol. In addition, manual tools take a long time, and the product needs to be evenly cooked, leaving a crust on the dodol stirring pan. To overcome this, an automatic stirring tool is needed at an affordable cost. Workers' participation as users is required so that the tools used match workers' wishes. Ergo-economic applications are necessary to meet workers' desires: comfort and affordable costs. From the evaluation carried out, it was found that the automatic stirring tool only requires a little energy because a machine does the stirring. This impacts the workload, fatigue, and complaints automatically decreasing when compared to using a manual stirring tool. Economically, the use of an automatic stirring tool provides benefits for dodol entrepreneurs after the 2.4th month. This is based on the investment value of the automatic stirring machine. The ROI (Return on Investment) level is 170.216%. This stirring machine is more effective because the stirring results are more even and do not cause crust on the container. Worker performance can be improved by applying ergo-economics based on preventive measures against behaviors that can potentially cause injury in the workplace. Workers are the main asset or economic resource in the industry, and ergonomics and economics are interrelated with ergonomics, which can create better working conditions, producing a better economy.